Registered Replication Report: Strack, Martin, & Stepper (1988). (November 2016) - Wagenmakers, E.-J.; Beek, T.; Dijkhoff, L.; Gronau, Q. F.; Acosta, A.; Adams, R. B.; Albohn, D. N.; Allard, E. S.; Benning, S. D.; Blouin-Hudon, E.-M.; Bulnes, L. C.; Caldwell, T. L.; et al.
According to the facial feedback hypothesis, people's affective responses can be influenced by their own facial expression (e.g., smiling, pouting), even when their expression did not result from their emotional experiences. For example, Strack, Martin, and Stepper (1988) instructed participants to rate the funniness of cartoons using a pen that they held in their mouth. In line with the facial feedback hypothesis, when participants held the pen with their teeth (inducing a "smile"), they rated the cartoons as funnier than when they held the pen with their lips (inducing a "pout"). This seminal study of the facial feedback hypothesis has not been replicated directly. This Registered Replication Report describes the results of 17 independent direct replications of Study 1 from Strack et al. (1988), all of which followed the same vetted protocol. A meta-analysis of these studies examined the difference in funniness ratings between the "smile" and "pout" conditions. The original Strack et al. (1988) study reported a rating difference of 0.82 units on a 10-point Likert scale. Our meta-analysis revealed a rating difference of 0.03 units with a 95% confidence interval ranging from −0.11 to 0.16.